TORA SULEIMAN'S LIONS IN THE UPBRINGING OF A HARMONIOUS HUMAN BEING SPIRITUAL AND EDUCATIONAL ASPECTS (Archive of Conferences, 2021)
This article emphasizes the unique style and unique approach of Tora Suleiman in Uzbekpoetry and his special place in folk melodies, as well as the special meaning and content of his poemsand the works he created